Placental elastography in a murine intrauterine growth restriction model†. (29th September 2015) - Quibel, T.; Deloison, B.; Chammings, F.; Chalouhi, G. E.; Siauve, N.; Alison, M.; Bessières, B.; Gennisson, J. L.; Clément, O.; Salomon, L. J.
Abstract: Objective: To compare placental elasticity in normal versus intrauterine growth restriction (IUGR) murine pregnancies using shear wave elastography (SWE). Methods: Intrauterine growth restriction was created by ligation of the left uterine artery of Sprague–Dawley rats on E17. Ultrasonography (US) and elastography were performed 2 days later on exteriorized horns after laparotomy. Biparietal diameter (BPD) and abdominal diameter (AD) were measured and compared in each horn. Placental elasticity of each placenta was compared in the right and left horns, respectively, using the Young's modulus, which increases with increasing stiffness of the tissue. Results: Two hundred seventeen feto‐placental units from 18 rats were included. Fetuses in the left ligated horn had smaller biometric measurements than those in the right horn (6.7 vs 7.2 mm, p  < 0.001, and 9.2 vs 11.2 mm, p  < 0.001 for BPD and AD, respectively). Mean fetal weight was lower in the pups from the left than the right horn (1.65 vs 2.11 g; p  < 0.001). Mean (SD) Young's modulus was higher for placentas from the left than the right horn (11.7 ± 1.5 kPa vs 8.01 ± 3.8 kPa, respectively; p  < 0.001), indicating increased stiffness in placentas from the left than the right horn. There was an inverse relationship between fetal weight and placental elasticity ( r  = 0.42; p  < 0.001). Conclusion: Shear wave elastography may be used to provide quantitative elasticity measurements of the placenta. In our model, placentas from IUGR fetuses demonstrated greater stiffness, which correlated with the degree of fetal growth restriction. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Placental insufficiency is the main cause of in utero growth restriction (IUGR). Ultrasonography and Doppler are commonly used in the diagnosis and management of IUGR. What does this study add? In an animal model, shear wave elastography provides quantitative elasticity measurements of the placenta.